The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.4314/wsa.v32i3.5276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solids retention time on <i>Microthrix parvicella</i> growth

Abstract: The objective of this study was to evaluate the effect of solids retention time (SRT) on M. parvicella growth and to calculate growth kinetic parameters of this filamentous species. Bench-scale continuous-flow experiments showed that M. parvicella growth can be significantly suppressed at an SRT of lower than 5.7 d for temperatures of between 14 and 18 o C. According to the continuous-flow experiments the maximum sludge age for the avoidance of filamentous foaming problems caused by M. parvicella is 6 d for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…decreasing mean cell residence time) (Noutsopoulos et al, 2006)  additional structures (e.g. classifying selectors) (Chudoba et al, 1973;Caravelli et al, 2003)  controlling dissolved oxygen levels in the pre-oxidation reactor (Pasinetti et al, 2005)  non-specific measures such as water sprays, steam application (Noutsopoulos et al, 2006).…”
Section: Non Specific Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…decreasing mean cell residence time) (Noutsopoulos et al, 2006)  additional structures (e.g. classifying selectors) (Chudoba et al, 1973;Caravelli et al, 2003)  controlling dissolved oxygen levels in the pre-oxidation reactor (Pasinetti et al, 2005)  non-specific measures such as water sprays, steam application (Noutsopoulos et al, 2006).…”
Section: Non Specific Methodsmentioning
confidence: 99%
“…Although the foaming bacteria grow faster on fatty, oily substances, they still grow relatively slowly as the fats, greases and oils are difficult to digest (Griffiths, 2010). It is suggested that the percentage of excessive bulking incidents is 10% to 29% for a SRT of greater than 8.5 d and filamentous bacteria requires a minimum sludge age of 10 days to grow and form a stable population (Griffiths, 2010) whereas there is no bulking occurs for SRTs of lower than 7 d (Noutsopoulos et al, 2006). Most early ASPs were focusing only on the biochemical oxygen demand (removal of organics) and operated at relatively short sludge ages of maximum 3 to 4 days.…”
Section: Causes Of Foamingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, M. parvicella, Type 0092 and Type 0041/0675 are grouped together (Group IV) as aerobic-anoxic-anaerobic-zone growers which are present in conditions of high solids retention, possibly utilising particulate substrates for growth (Martins et al, 2005). Although BNR WWTWs with low F/M ratios, high solids retention times and predominantly particulate and slowly biodegradable COD (SBCOD) have been associated with the selection of Type 0092 (Eikelboom, 2000;Casey et al, 1999aCasey et al, , 1999bCasey et al, , 1999cJenkins et al, 2004;Martins et al, 2003), there is also research which discounts the influence of F/M ratio on the selection process (Noutsopoulos et al, 2006).…”
Section: Eikelboom Type 0092mentioning
confidence: 99%
“…High concentrations of fatty acids are formed when there are long retention times in sewers, primary settling tanks or anaerobic zones, which provide ideal conditions for the proliferation of M. parvicella (Jenkins et al, 2004). Under laboratory conditions, it has been shown that foaming problems due to M. parvicella at low temperatures can be alleviated by reducing the age of the sludge to change the morphology of the filament (Noutsopoulos et al, 2006), and that that the presence of free ammonia as a source of nitrogen can cause bulking by M. parvicella (Tsai et al, 2003). Specific strategies that either have been used (with varying degrees of success) or show promise for the control of filamentous overgrowth of M. parvicella include: reducing solids retention times, using pre-flotation to reduce the lipid fraction, increasing the dissolved oxygen concentration (ideally by employing selectors), and adding polyaluminium hydrochloride (Jenkins et al, 2004;Madoni and Davoli, 2002;Nielson et al, 2002;Roels et al, 2002).…”
Section: Microthrix Parvicellamentioning
confidence: 99%